Effect of supercooling storage applied with stepwise algorithm for fishes (salmon and olive flounder) and its freshness during extended storage - Park, Dong Hyeon; Lee, SangYoon; Byeon, Yeong Mi; Kim, Eun Jeong; Choi, Mi-Jung (Food bioscience, 2022)
Supercooling storage reduces the temperature of a product by lowering its freezing point without phase transition and may extend its shelf life. However, it is difficult to maintain the supercooled state of food as it is thermodynamically metastable. A slow cooling rate and minimal fluctuation are essential for achieving stable supercooling storage. Therefore, a stepwise algorithm was adopted for supercooling storage in this study. Salmon and olive flounder were stored at 3 °C (refrigeration), −18 °C (freezing), and −2 °C (supercooling) for 12 days. Samples were maintained in a supercooled state and unfrozen during the storage period. Samples stored after the supercooling treatment were superior with respect to drip loss and water holding capacity (WHC) compared to frozen samples, regardless of the type of sample. WHC and total volatile basic nitrogen values of olive flounder was higher than those in salmon owing to the higher water and protein content in olive flounder than in salmon. Moreover, the supercooled samples inhibited the increase in trimethylamine and volatile basic nitrogen levels. Microbial growth was slow. Thus, a stepwise algorithm for stable supercooled storage was achieved, which effectively preserved fish quality better than freezing and refrigeration storage.